Seasonal profiles of Aedes aegypti (Diptera: Culicidae) larval habitats in an urban area of Costa Rica with a history of mosquito control - Troyo Rodríguez, Adriana (2008)
Dengue is the most important arboviral disease worldwide and the principal vector-borne disease in Costa Rica. Control of Aedes aegypti populations through source reduction is still considered the most effective way of prevention and control, although it has proven ineffective or unsustainable in many areas with a history of mosquito control. In this study, seasonal profiles and productivity of Aedes aegypti were analyzed in the city of Puntarenas, Costa Rica, where vector control has been practiced for more than ten years. Households contained more than 80% of larval habitats identified, although presence of habitats was more likely in other locations like lots and streets. In the wet season, habitats in the “other” category, like appliances, small manholes, and miscellaneous containers, were the most frequent habitats observed as well as the most common and productive habitats for Ae. aegypti. In the dry season, domestic animal drinking containers were very common, although concrete washtubs contained 79% of Ae. aegypti pupae collected. Individually, non-disposable habitats were as likely or more likely to contain mosquito larvae, and large containers were more likely to harbor mosquito larvae than the small ones only in the dry season. Considering various variables in the logistic regressions, predictors for Ae. aegypti in a habitat were habitat type (p<0.001), setting (p=0.043), and disposability (p=0.022) in the wet season and habitat capacity in the dry season (p=0.025). Overall, traditional Ae. aegypti larval indices and pupal indices in Puntarenas were high enough to allow viral transmission during the wet season. In spite of continued vector control, it has not been possible to reduce vector densities below threshold levels in Puntarenas, and the habitat profiles show that non-household locations, as well as non-disposable containers, should be targeted in addition to the standard control activities.